Innovate to eliminate: a prerequisite in NTD programmes. (21st September 2022) - Rust, Jennifer; Clark, Amy; Woodgate, Mary; Koch, Christina; Mohammed, Taylor; Steinmann, Peter; Krentel, Alison; Torres-Vitolas, Carlos A; Carlin, Alexandra; Pavluck, Alexandre
Abstract: Innovation plays a critical role in progress towards achievement of the World Health Organization's road map for neglected tropical diseases 2021–2030. As disease prevalence decreases, the cost to identify and treat remaining cases goes up. Additionally, as programmes move to the surveillance phase, diagnostic tests need to be highly sensitive and affordable. Until the early end to the Ascend West and Central Africa programme, the Ascend Learning and Innovation Fund supported five projects from 2019 to 2021. Designed for innovation, the fund encompassed a range of activities, including operational research, product development and social behavioural change. This flexibility allowed innovation to bridge the gap between strategic policy and practical implementation, piloting and proving business models to respond to information found through Ascend.